THE COHERENCE-BASED STRATEGY TO TEACH ADVANCED WRITING TO INDONESIANS (Universitas Negeri Semarang, 2012)
In this era, English is established as the world language of research and publication. This makes the English language significant for students and professionals. According to Storrer (2002: 1), authors should design a text in such a way that the addressee may detect the relationships linking individual text constituents. In other words, the authors should write a coherent text. Coherence is a key concept for text comprehension and text clarity. This research is aimed at finding out the coherence level of the English Arguments of Indonesian writers found in the Opinion Forum of The Jakarta Post. This research applies topical, paradigmatic analysis. It involves identifying topics and sequences of topics/ ideas. The coherence parameters offered by scholars are applied to classify the data. The research results show that English Arguments of Indonesian writers are mostly developed partly coherently. The main features that reduce the text coherence are the insufficient textual cohesion markers and the incompleteness of paragraph development. On the basis of the research findings, the coherence-based approach to teach Advanced Writing is designed. It is suggested that the teachers apply the coherence-based teaching as an alternative teaching strategy in order that they can offer more constructive help to their students.